User's guide to Sears list of subject headings - Satija, Mohinder Partap 1949- (Rowman & Littlefield, 2020)
Covers "the importance of vocabulary control, the process of subject analysis, the structure and organization of the Sears List, and the methods to locate, specify, and construct subject headings and provide cross references for the public catalog."--Back cover.